Identifikasi dan Sebaran Intrusi Air Laut terhadap Airtanah Dangkal di Kota Kendari Sulawesi Tenggara - Kete, Surya Cipta Ramadhan; Suprihatin, Suprihatin; Tarigan, Suria Darma; Effendi, Hefni (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2020)
ABSTRACTThe availability of clean water is one of the main problems for the people in Kendari City. Overutilization of groundwater can cause seawater intrusion to groundwater. This study aims to identify and map seawater intrusion distribution to shallow groundwater based on water quality data.Ã‚Â Sampling was obtained from 100 dug wells of the inhabitant (n=100) in March-July 2019 with a variation of the distance from the beach 0.04-5.52 km and the elevation of Groundwater (MAT) between 0.43-30.01 MASL. The distribution of shallow groundwater is mapped on the criteria to the value of Electrical Conductivity (DHL) at the standard temperature of 25 Ã‚Â°C. The analysis showed that the average groundwater temperature was 29.28Ã‚Â Ã‚Â°C, DHL was 393.52 Ã‚Âµmhos, Total Dissolved Solid (TDS) was 196.98 ppm, and pH was 6.31. Shallow groundwater, which has been varied intruded with high intruded (26.26%), rather high intruded (14.14%), medium intruded (32.32%), low intruded (6.06%) and not intruded (21.21%). The correlation between distance from the coast to the value of DHL was not significantly correlated (R2 =Ã‚Â -0.49), while groundwater level elevation has a significant correlation (R2 = 0.71). The geological factors of alluvial deposits, which generally have low permeability and slope to flat topography, cause seawater intrusion to shallow groundwater.Keywords:Ã‚Â sea water intrusion, shallow groundwater, Kendari CityÃ‚Â ABSTRAKKetersediaan air bersih merupakan salah satu masalah utama bagi masyarakat kota Kendari. Sumber air bersih masyarakat diperoleh dari airtanah. Pemanfaatan airtanah yang berlebihan dapat menyebabkan terjadinya intrusi air laut terhadap airtanah. Penelitian ini bertujuan untuk mengidentifikasi dan memetakan sebaran intrusi air laut terhadap airtanah dangkal berdasarkan data kualitas air. Pengambilan sampel diperoleh dari sumur gali penduduk sebanyak 100 sampelÃ‚Â (n=100) pada periode Maret-Juli 2019 dengan variasi jarak dari pantai 0,04-5,52 kmÃ‚Â dan elevasi muka airtanah (MAT)Ã‚Â antara 0,43-30,01 mdpl. Hasil analisis menunjukan bahwa rerata suhu airtanah sebesar 29,28Ã‚Â Ã‚Â°C, DHL sebesar 393,52 Ã‚Âµmhos, Total Dissolved SolidÃ‚Â (TDS) sebesar 196,98 ppm dan pH sebesar 6,31. Airtanah dangkal secara umum telah terintrusi dengan variasi meliputi terintruksi tinggi (26,26%), terintrusi agak tinggi (14,14%), terintrusi sedang (32,32%), terintrusi sedikit (6,06%) dan tidak terintrusi (21,21%). Korelasi antara jarak dari pantai terhadap nilai DHL tidak signifikan (R2 = -0,49), sedangkan MAT memiliki korelasi signifikan (R2= 0,71). Faktor geologi berupa endapan alluvial yang memiliki permeabilitas umumnya rendah dan berada pada topografi landai hingga datar menyebabkan terjadinya intrusi air laut terhadap airtanah dangkal.Kata Kunci:Ã‚Â intrusi air laut, airtanah dangkal, Kota Kendari